2007
DOI: 10.1007/bf03000187
|View full text |Cite
|
Sign up to set email alerts
|

Emotional support for men and women with cancer: Do patients receive what their partners provide?

Abstract: such as their network of friends or professional help, may need to be identified. A couple-coping intervention could be implemented to help partners learn about each other's needs in times of crisis and ways to cope with adversity. Key words: social support, spouses, cancer, coping, couples, dyadic copingDiagnosis and treatment of cancer are challenging to both patients and their partners. An acute medical situation can turn into a chronic condition when treatment is not successful or when side effects of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
(28 reference statements)
3
27
0
1
Order By: Relevance
“…Social support was measured by the Berlin Social Support Scales (BSSS) [10] with 15 items, rated on a fourpoint scale from '1, don't agree' to '4, agree completely', constituting four factors: (1) emotional support, (2) instrumental support, (3) informational support and (4) satisfaction with support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support was measured by the Berlin Social Support Scales (BSSS) [10] with 15 items, rated on a fourpoint scale from '1, don't agree' to '4, agree completely', constituting four factors: (1) emotional support, (2) instrumental support, (3) informational support and (4) satisfaction with support.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on how sex-specific psychosocial variables impact on metabolic control is not yet available. Although patient-oriented education geared to selfmanagement improves treatment adherence and glycaemic control in patients with type 2 diabetes [9], it is still unclear whether sex-specific differences affect compliance with diabetes management and/or strategies for coping with the disease, including depressive or active approach, problemoriented behaviour or distraction, and religiosity or wishful thinking [10].…”
Section: Introductionmentioning
confidence: 99%
“…Validity and reliability had been previously demonstrated [7], and reliability was acceptable in this study (Cronbach's α ≥ 0.85). bsss has been used before in patients with cancer and their caregivers [8].…”
Section: Participantsmentioning
confidence: 99%
“…Social support is seen as one of the key factors to successfully overcome health compromising behaviors (e.g., McAuley et al 2003) and to cope with illnesses or functional limitations (Luszczynska et al 2007;Knoll et al 2007a). However, in a literature review on the effectiveness of social support interventions, Hogan et al (2002) reported mixed results.…”
Section: Social Integration and Social Supportmentioning
confidence: 99%